(untitled) (Revista Brasileira Multidisciplinar, 2025)
The study addresses the leisure practices of youth skateboarders and their relationship with the occupation of urban spaces. The article’s objective is to conduct a review of studies investigating skateboarding as a physical practice and its interaction with territory. The methodology involved the analysis of 26 studies, including 18 articles, 6 dissertations, and 2 theses, categorizing the most recurrent terms in the conclusions of these works. The results highlight three main categories: the skateboarders themselves, the spatial context of their practices, and skateboarding as an activity that goes beyond sport. It was observed that skateboarders reconfigure urban spaces, transforming them into territories of leisure and sociability. Additionally, the studies indicate that public policies aimed at urban leisure are still limited and deserve greater attention. The article concludes that youth skateboarders challenge urban order by reinterpreting public space, bringing important reflections on territory, identity, and leisure.